2014
DOI: 10.1002/mus.24141
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, electrophysiologic, and imaging features of zoster‐associated limb paresis

Abstract: ZALP is associated with considerable weakness. It typically lasts at least several months, localizes to plexus or peripheral nerve in 63%, and is associated with high rates of PHN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
44
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 26 publications
2
44
0
3
Order By: Relevance
“…Functional improvement occurs between 1 and 2 years in most cases [10]. Our patient showed a remarkable improvement pattern 4 months after the onset.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Functional improvement occurs between 1 and 2 years in most cases [10]. Our patient showed a remarkable improvement pattern 4 months after the onset.…”
Section: Discussionsupporting
confidence: 52%
“…In a study which evaluated 49 patients with zoster associated limb paralysis in 2014, Jones et al [10] reported that the mean age of onset was 71 years; the duration between rash and weakness was approximately 5.8 days; and 11% of patients had diabetes mellitus. The mean duration of paralysis was days.…”
Section: Discussionmentioning
confidence: 99%
“…Acute rash is often preceded by pain in the corresponding dermatome. Diffuse lumbosacral plexus involvement may occur in approximately 20% of lumbosacral region reactivations 5. Motor neuropathy and paresis secondary to either plexopathy or single neuropathy occurs in 1%–20% of confirmed VZV reactivations 1…”
Section: Discussionmentioning
confidence: 99%
“…There are few published case reports and series describing zoster associated lower limb plexopathy,5 likely due to the rarity of the condition. As such, there is no consensus guideline for the long-term management of the condition, especially with respect to reducing the risk of long-term neuralgia.…”
Section: Discussionmentioning
confidence: 99%
“…Weakness associated with HZ has been recognized since the 19th century and can affect bulbar, limb, or truncal muscles. 7 The incidence of SMP may increase with EDX studies revealed that subclinical motor involvement is more prevalent in patients with zoster infection. However, plexopathy presenting with severe motor paralysis due to zoster infection has been rarely described.…”
mentioning
confidence: 99%